2018
DOI: 10.1186/s12711-018-0413-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of variance components and prediction of breeding values based on group records from varying group sizes

Abstract: BackgroundRecords on groups of individuals rather than on single individuals could be valuable for predicting breeding values (BV) of the traits that are difficult or costly to measure individually, such as feed intake in pigs or beef cattle. Here, we present a model, which handles group records from varying group sizes and involves multiple fixed and random effects, for estimating variance components and predicting BV. Moreover, using simulation, we investigated the efficiency of group records for predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 21 publications
5
28
0
Order By: Relevance
“…The estimates of variance components (mean (SD) over 50 replicates) in scenario S 12 L 2 × 3 (group size = 12, individuals from four litters per pen) for trait 1 and trait 2 using multivariate model based on group or individual records with different proportion of individuals having genotypes. Many studies have concluded that closer relationships between individuals in each group results in more accurate EBVs (Olson et al 2006;Peeters et al 2013;Su et al 2018). Consistent results were obtained in our study.…”
Section: Tablesupporting
confidence: 92%
See 1 more Smart Citation
“…The estimates of variance components (mean (SD) over 50 replicates) in scenario S 12 L 2 × 3 (group size = 12, individuals from four litters per pen) for trait 1 and trait 2 using multivariate model based on group or individual records with different proportion of individuals having genotypes. Many studies have concluded that closer relationships between individuals in each group results in more accurate EBVs (Olson et al 2006;Peeters et al 2013;Su et al 2018). Consistent results were obtained in our study.…”
Section: Tablesupporting
confidence: 92%
“…When trait 1 was measured on groups (pens), the model for the group records can be written as shown by Su et al (2018)…”
Section: Univariate Analysismentioning
confidence: 99%
“…In this study, we have reported variance components and genetic parameters of several measurements of feed efficiency obtained from a model that combines group/cage records of FI and individual records of G and M, under two different feeding regimens commonly applied in rabbit meat production farms. This procedure overcomes difficulties for identification of genetic and environmental random effects of FI when group records are used, as was discussed by Su et al (). In addition, it takes advantage of the definition of FE traits as selection indexes that can be obtained from multiple‐trait genetic evaluations (Kennedy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even in the situation in which electronic feeders are available, it is interesting to explore other sources of information which are less expensive than FI records obtained with them, as it could be FI recorded at the group level (Su et al, ). Several studies have reported models for the estimation of genetic parameters and variance components of FI using group data (Biscarini, Bovenhuis, & Arendonk, ; Cooper, Ferrell, Cundiff, & Vleck, ; Olson, Garrick, & Enns, ; Shirali et al, ; Su et al, ) but only Shirali et al () combine individual records of production traits and group records of FI in a single‐trait model defining phenotypic RFI from a phenotypic regression model of cage FI on body weight of each of the two cage mates. This situation is similar to ours but in our case, given that groups are larger (8 cage mates), the number of available cage records is limited (321).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation